Optimization of the Urea SCR injector based on entropy generation minimization and entransy dissipation extremum. (15th May 2023) - Ye, Jiedong; Tan, Gangfeng; He, Zixuan; Alex, Frimpong J.; Peng, Dengzhi; Zhang, Zhiqing
Highlights: ANN model predicted UWS heat transfer results with a max error of less than 9.3%. The UWS heat transfer was optimized based on EDE and EGM respectively. Optimize EDE better than EGM, ui 0.724% higher, NH3 214 ppm higher. Abstract: A urea injection model with a mixer was established, and the of the urea-water-solution (UWS) heat transfer behavior in the pipeline was studied using the ML-CFD method, The influence of the urea injector parameters on NH3 concentration and uniformity was analyzed through parameter analysis. To improve the quality of NH3 produced by the UWS, according to the heat transfer efficiency of UWS in the pipeline, the parameters of the urea injector were optimized with the mutil-objectives of entropy generation minimization (EGM) and entransy dissipation extremum (EDE) respectively. The corresponding Pareto front was obtained, and the CFD model was established to compare the application of the two heat transfer indicators in engineering practice. The results show that both the EGM and the EDE methods can effectively optimize the heat transfer of UWS in the flow field, but the EDE method is better than EDG. The uniformity is 0.724% higher, and the NH3 concentration is 6.411% higher. This provides technical support for enhancing the UWS heat transfer. Graphical abstract: Image, graphical abstract